Implementation Of The Islamization Curriculum In Islamic Religious Higher Education (PTKI) Development In Indonesia As An Effort To Integrate Science In The Perspective Of Maqasid Al-Shari'ah - Putri Silaturrahmi; Uswatun Hasanah; Muhammad Abdul Aziz (AL-WIJDÃN Journal of Islamic Education Studies, 2023)
In the present period, Islamic education has significant difficulties. The challenge born in this era is to withstand the exposure of western secularism. PTKI as the axis of higher-level religious education must be able to apply the model of Islamization of education at the university level. In order to apply the Islamization curriculum in higher education, Abdul Hamid Abdul Sulayman a person who is much influenced by Syed Qutub's ideas, is attempting to establish islamization curriculum at the International Islamic University Malaysia (IIUM). With this implementation, AHAS as a policy actor hope to produce Muslim scholars who have a universal perspective of Maqasid Al-Shariah. Meanwhile in Indonesia itself the biggest potential of Muslim world needs to elaborate more regarding to the impelementation of islamization curriculum in PTKI. Using library study this research had been conducted. This research found that PTKI plays an education strategy following the roots of Islamic Curriculum (Isamic-National-International Curriculum). The curriculum has the potential to raise a generation of Muslims capable of using their faith to help solve humanitarian problems through the Maqasid Al-Shariah method. Furthermore, this education model will reform PTKI so that it may generate scholars who are specialists in religious sciences, as well as experts in religious sciences and general sciences.   Keywords: PTKI Curriculum, Integration Science, Maqasid al-Shariah.